Application of RAPD-PCR and Phylogenetic Analysis for Accurate Characterization of Salmonella spp. Isolated from Chicken and Their Feed and Drinking Water - Hasan, Thamer O; J Lafta, Inam; A Ahmed, Emad; A Jassam, Samah (The Iraqi Journal of Veterinary Medicine, 2023)
The aim of this study was ‎the‎ discrimination of Salmonella‎‎ isolated from chicken and their feed ‎and drinking water for the epidemiological control of salmonellosis. Totally, 289 samples, ‎including 217 chicken cloaca swabs, 46 water, and 26 feed samples were collected from five ‎different farms in Karbala governorate, Iraq. Conventional bacteriology tests, API 20E, Vitek 2, ‎and serology were used for bacterial identification. Random amplified polymorphic ‎DNA (RAPD)-polymerase chain reaction (PCR) was applied to analyze the genetic relationships ‎among Salmonella‎‎ isolates. The isolation rate of Salmonella‎‎ spp. was 21.1% (61/289). While the ‎water samples constituted the highest rate (30.4%), a rate of 21.7% was reported for the cloaca ‎swabs, with no isolate at all from chicken feed. Vitek 2 was able to identify some isolates to the ‎serotype level, such as S. Enteritidis, S. Paratyphi B, and S. Paratyphi C. However, the isolates ‎were diagnosed as S. enterica by API 20E, and as S. enterica subsp. arizonae through serology. ‎Analyzing the samples by the RAPD-PCR assay showed the presence of genetically different ‎Salmonella‎‎ spp. Dendrograms created by the GelJ software successfully delineated the genetic ‎relationships. Therefore, RAPD-PCR can be used as a surrogate tool for the fast, reliable, and ‎accurate detection of Salmonella‎‎ in epidemiological surveys when compared with other ‎biochemical-based identification methods.